Capacidade de cocção de grãos de feijão em função do genótipo e da temperatura da água de hidratação - Coelho, Cileide Maria Medeiros (2008)
The objective of this work was to evaluate the effect of temperature of the soaking water in the capacity of hydration and time of cooking in which way it may be an indicative of lower cooking time for common bean grains. Five cultivars were used: Rubi, Uirapuru, Pérola, Valente, and Campeiro, produced in commercial farmings in Lages SC, in the season of 2005/2006. The fresh grains were previously standardized for 12% of humidity and analyzed to hydration time, hydration capacity and cooking time. The increase of temperature in the soaking water provided an increase in the hydration capacity differently to each cultivar, with temperature higher than 25ºC. Pérola took around 8 hours to reach the maximum hydration, while Rubi, in this same condition, did not reach the maximum hydration. The correlation analysis showed that only for cultivars Campeiro and Rubi the fast water absorption by the grains is an indicative of higher cooking capacity, but a negative correlation was observed for Uirapuru. Based on the evaluated genotypes, it is improbable to make only one standardization of the previous conditions for the cooking that is valid to all cultivars, that is, a detailed and specific characterization is necessary to each genotype in study.